Analisis Pengendalian Persediaan Bahan Baku dengan Menggunakan Metode Material Requirement Planning pada UMKM Onde-Onde Liana di Sragen - Sri Rejeki, Putri; Sunarso (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Liana Onde-onde, a micro, small, and medium-sized enterprise (MSME) in the food production industry, faces challenges in managing raw material inventory costs. This research aims to analyze the extent to which the existing inventory control system has achieved optimal efficiency. Furthermore, this study will explore the implementation of the Material Requirements Planning (MRP) method as an alternative to improve the efficiency of raw material inventory costs at the MSME. This research adopts the Material Requirements Planning (MRP) approach in the context of Liana Onde-onde production. The data collected includes company profiles, process production analysis, raw material quantification, inventory, and evaluation of storage and ordering costs. Data sources include direct observation and internal documentation. Data collection methods involved in-depth interviews and document studies. Quantitative analysis uses lot sizing techniques, namely Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The results of the study conclude that the raw material control system of Liana Onde-onde is not yet efficient. This is evidenced by the total raw material inventory costs incurred according to Liana Onde-onde's policy, resulting in a total raw material inventory cost of Rp. 1,525,000, which is greater than the Lot For Lot (LFL) technique of Rp. 240,000, the Economic Order Quantity (EOQ) of Rp. 1,028,000, and the Period Order Quantity (POQ) of Rp. 240,000. From the comparison, the Period Order Quantity (POQ) technique produces the most efficient total raw material inventory cost.